Productive, behavioral and physiological performance of feedlot Guzerat and ½ Guzerat Ã— ½ Aberdeen Angus cattle - Ferro, Diogo Alves da Costa; Ferro, Rafael Alves da Costa; Santos, Aracele Pinheiro Pales dos; Taveira, Rodrigo Zaiden; Silva, Bruna Paula Alves da; Santos, Klayto José Gonçalves dos; Rosa, Geovana Gonçalves; Contijo, Lídia Mendes de Aquino (Semina: Ciências Agrárias, 2020)
The objective of this study was to compare the productive, behavioral and physiological performance of feedlot Guzerat and ½ Guzerat Ã— ½ Aberdeen Angus cattle. The experiment was conducted in a commercial feedlot for 80 days, between April and June 2016. Fifteen male Guzerat and 15 male ½ Guzerat-Aberdeen Angus cattle, both at the same age, with respective average initial weights of 381.27 and 401.34 Â± 54.70 kg, were used. The animals were kept in collective pens, one for each breed group, with 14 m2 available per animal. Environmental conditions, respiratory frequency and behavior were evaluated for 12h00, starting at 06h00 and ending at 18h00. Feeding, rumination, rest, other activities and social, body care, anomalous, playful and locomotion behavior were observed. To examine the productive responses, initial weight, final weight, average daily weight gain, total weight gain, carcass yield, conformation and fatness were measured. Behaviors referring to feeding, rumination and other activities did not differ between the breed groups, except for the rest, playful and locomotion behaviors. A significant difference was detected (p < 0.05) for respiratory frequency and productive characteristics between the breed groups. In conclusion, ½ Guzerat Ã— ½ Aberdeen Angus were superior to Guzerat cattle in productive performance. However, for behavioral and physiological variables, Guzerat animals exhibited better performance.